Future of Food : Building Stronger Food Systems in Fragility, Conflict, and Violence Settings - Townsend, Robert; Verner, Dorte; Adubi, Abimbola; Saint-Geours, Jean; Leao, Izabela; Juergenliemk, Armine; Robertson, Tim; Williams, Melissa; de Preneuf, Flore; Jonasova, Marketa; Carmichael, Zacharey (World Bank, Washington, DC, 2021)
Achieving the UN Sustainable Development Goals is impossible without addressing fragility, conflict, and violence (FCV), especially as two thirds of the extreme poor are projected to live in such situations by 2030. Conflicts as well as climatic and natural hazards displace millions of people each year. Strengthening food systems can be an essential lever of change that contributes to ending poverty while maintaining and restoring peace. This paper focuses on how stabilizing and improving food systems can have a positive impact in FCVs settings, not just by preventing hunger, but by creating employment and increasing shared prosperity, which may contribute to greater peace. It reflects the four pillars of the World Bank Group Strategy for Fragility, Conflict, and Violence 2020-2025 – promote prevention, remain engaged in crisis situations and conflict, help countries transition out of fragility, and mitigate spillover impacts. To strengthen food systems across the spectrum of FCV settings, the paper highlights four key areas of focus for practitioners: (i) strengthening governance and institutional capacity by supporting food programs such as those that focus on the welfare of the entire population, rather than just a fraction of it; (ii) preventing and responding to food crises to avoid not only hunger, but also people sliding deeper into poverty; (iii) growing the private sector through agribusiness development, inclusive jobs in agricultural value chains, particularly for women and youth, and rural livelihoods to break the cycle of intergenerational poverty common in FCV settings; and (iv) reducing conflict risk and environmental fragility through resilient and sustainable resource management in ways that help build government legitimacy. This paper is rich in practical and tested examples across FCV settings from around the world and makes a strong case for providing development support and assistance in these challenging environments. By setting food systems up for success, governments can invest in the essential foundations of peace and prosperity.